Comparative Genomics of the Listeria monocytogenes ST204 Subgroup - Fox, Edward M.; Allnutt, Theodore; Bradbury, Mark I.; Fanning, Séamus; Chandry, P. Scott (Frontiers in Microbiology, 2016)
The ST204 subgroup of Listeria monocytogenes is among the most frequently isolated in Australia from a range of environmental niches. In this study we provide a comparative genomics analysis of food and food environment isolates from geographically diverse sources. Analysis of the ST204 genomes showed a highly conserved core genome with the majority of variation seen in mobile genetic elements such as plasmids, transposons and phage insertions. Most strains (13/15) harbored plasmids, which although varying in size contained highly conserved sequences. Interestingly 4 isolates contained a conserved plasmid of 91,396 bp. The strains examined were isolated over a period of 12 years and from different geographic locations suggesting plasmids are an important component of the genetic repertoire of this subgroup and may provide a range of stress tolerance mechanisms. In addition to this 4 phage insertion sites and 2 transposons were identified among isolates, including a novel transposon. These genetic elements were highly conserved across isolates that harbored them, and also contained a range of genetic markers linked to stress tolerance and virulence. The maintenance of conserved mobile genetic elements in the ST204 population suggests these elements may contribute to the diverse range of niches colonised by ST204 isolates. Environmental stress selection may contribute to maintaining these genetic features, which in turn may be co-selecting for virulence markers relevant to clinical infection with ST204 isolates.